Social Insecurity at The Intersection of Disabilities and Poverty in John Steinbeck’s of Mice and Men - Melania Priska Mendrofa (Jurnal Multidisiplin Madani, 2021)
Poverty is much experienced by disabled people and vice versa. Having less or even no chance to public access has caused the feeling of uncertainty and social unworthiness. Social insecurity triggers anxiety about everything, and mostly about people’s self-confidence to create a relationship with others. Of Mice and Men represents society’s bad treatment for two disabled characters. The paralyzed condition, which is also worsened by their low-financial status, makes the two characters have some problems in adapting themselves to society. This paper aims to discuss kinds of social insecurity constituted at the intersection of disabilities and poverty using qualitative research analysis and descriptive methods. Intersectionality theory helps this paper to see and understand how oppression is formed because of people’s multiple identities. The result of this paper showed that the multiple identities of disabled people become barriers that give them the feeling of insecure to build relations with others and improve their life.